Adjuvant radiotherapy in node positive prostate cancer patients: a debate still on. when, for whom?. (25th September 2020) - Marvaso, Giulia; Montesano, Marianna; Corrao, Giulia; De Angelis, Simone P.; Gandini, Sara; Mazzola, Giovanni C.; Augugliaro, Matteo; Franzetti, Jessica; Zerini, Dario; Pepa, Matteo; Luzzago, Stefano; Mistretta, Francesco A.; et al.
Abstract : Objective: To evaluate the impact of adjuvant radiotherapy (aRT) in patients with prostate cancer (PCa) found to have pathological positive lymph nodes (pN1s) after radical prostatectomy (RP) and extended pelvic lymph node dissection (ePLND) with regard to distant recurrence‐free survival (RFS), according to both main tumour pathological characteristics and number of positive lymph nodes. Biochemical RFS, local RFS, overall survival (OS) and acute and late toxicity were assessed as secondary endpoints. Patients and Methods: A retrospective cohort of 187 consecutive patients with pN1 PCa were treated with aRT at the IEO, European Institute of Oncology IRCCS, Milan, Italy. aRT on the tumour bed and pelvis was administered within 6 months of RP. Androgen deprivation therapy was administered according to the guidelines. Univariate and multivariate Cox regression analyses predicting biochemical RFS, local RFS, distant RFS and OS rates were performed to assess whether the number of pN1s represented an independent prognostic factor. The Youden index was computed to find the optimal threshold for the number of pN1s able to discriminate between patients with or without biochemical and clinical relapse. Results: At 5 years, local RFS, distant RFS, biochemical RFS and OS were 68%, 71%, 56% and 94%, respectively. The median follow‐up was 49 months. The number of pN1s was significantly associated with biochemical RFS, local RFS and distant RFS. The best threshold for discriminating between patients with or without biochemical and clinical relapse was five pN1s. In multivariate analyses, the number of pN1s was confirmed to be an independent predictor of biochemical RFS, local RFS and distant RFS, but not of OS. Multivariate analyses also showed an increased risk of biochemical relapse for increasing values of initial prostate‐specific antigen and for patients with tumour vascular invasion. Local and distant RFS were also inversely correlated with significantly reduced risk for International Society of Urological Pathology grade group <3 (group 1 or 2 compared to group 3). Conclusions: Our data confirmed the encouraging outcomes of patients with pN1 PCa treated with adjuvant treatments and the key role represented by the number of pN1s in predicting biochemical RFS, clinical RFS and distant RFS. Large prospective cohort studies and randomized clinical trials are needed to confirm these results and to identify the subgroup of patients with pN1 PCa who would most benefit from aRT.